(untitled) (Eduscotech, 2022)
The art of Turangga Seto, Samiran Village, Selo District, Boyolali Regency in its presentation uses several Javanese gamelan instruments of the bonangan type consisting of drums, bonang, demung, saron kenong kempul and gongs. In addition, several musical instruments were also added, such as: drums, kibot, tambourines, and cymbals, with Surakarta-style songs (gending), with dashing dance moves, and gecul. Turonggo Seto dance is an inseparable part of the Rejeban ceremony which is always carried out in conjunction with the village clean ceremony, Samiran Village, Sela District, Boyolali Regency. is a means of connecting humans with supernatural powers in a mystical way. Turonggo Seto is a bridge of requests from humans with their ancestors, the baurekso dahyangs, villages, mountains, and roads. In addition to being a means of expressing gratitude to God Almighty for his bounty with abundant harvests and for the fertility of his land. The presence of the traditional performing arts of Turonggo Seto is not only for entertainment, but also as a complement to the needs of social activities. Therefore, it can be said that the Turonggo Seto dance performance is one of the ritual expressions and performances of the people of Samiran Village. Expression as a ritual is to meet the emotional needs of the belief or belief system that exists, on the other hand as a performance that is deliberately arranged by the people of Samiran Village to meet aesthetic needs (entertainment or spectacle) that can be enjoyed by actors (players) and spectators.